A STUDY ON STRESS MANAGEMENT OF IT EMPLOYEES AT CHENNAI DISTRICT - Dr.K.Gunasekaran, Dr.P.Elantheraiyan (International Journal of Advanced Science and Technology, 2020)
Stress management may be regarded as an important technique and measurement which enhances the overall performances of the employee and improves his productivity and quality of work. Stress is a feeling that creates physiological and psychological imbalance with in a person it’s a body response any demand of changes in internal and external environment.